Improvement of methods for description of a three-bunker collection conveyor - Pihnastyi, Oleh; Chernіavska Svіtlana (Eastern-European Journal of Enterprise Technologies, 2022)
The object of current research is a multi-section transport conveyor. The actual control problem of the flow parameters of a multi-section conveyor-type transport system with a given control quality criterion is solved. Algorithms for optimal control of the flow of material coming from the input accumulating bunkers into the collection section of the conveyor, ensuring the filling of the accumulating tank in the minimum time were synthesized. An admissible control of the material flow from the accumulating bunkers is found, which allow filling the accumulating tank, taking into account the given distribution of the material along the section of the collection conveyor at the initial and final moments of the filling time with minimal energy consumption. The synthesis of algorithms for optimal control of the material flow from accumulating bunkers became possible due to the determination of differential constraints in the optimal control problem based on an analytical distributed model of a transport conveyor section. The distinctive features of the results obtained are that the allowable controls contain restrictions on the maximum allowable load of material on the conveyor belt and take into account the initial and final distribution of material along the collection conveyor section. Also, a feature of the obtained results is the consideration of variable transport delay in the transport conveyor control model. The application area of the results is the mining industry. The developed models make it possible to synthesize algorithms for optimal control of the flow parameters of the transport system for a mining enterprise, taking into account the transport delay in the incoming of material at the output of the conveyor section. The condition for the practical use of the results obtained is the presence of measuring sensors in the sections of the transport conveyor that determine the belt speed and the amount of material in the accumulating bunkers.